5 - (Re)produire, marquer et (s’)approprier des « lieux (publics) de ville » par les mots ou comment les murs (dé)font les langues à Dschang - Tsofack Jean-Benoît (Africa Development, 2021)
In this contribution, we examine the linguistic ‘disorder’ in a Cameroonian city marked by multilingualism. In other words, we look into how city walls (signs or advertisements) make languages, i.e. how they construct heterogeneous linguistic practices, but also how those same walls unmake languages, by changing them ‘unconsciously and permanently’ or, a contrario, how languages make or unmake walls. We therefore observe that the public space is also a ‘discursive space’ and the very locus of the linguistic ‘disorder’ where what is important is not what people say or write, but rather how they speak and write, how they communicate ‘in this disorder, or despite this disorder, or even through this disorder’, how languages are publicly ‘staged’ and displayed. Based on indirect ‘observation’ of linguistic practices carried out, we used an ‘unsolicited’ corpus of advertising discourse (various signs and place names) gathered during a field survey conducted in 2007 in the city of Dschang. Our overall methodology pertains to Discourse Analysis as conceived by Bulot and Veschambre (2006b), i.e. an analysis of the ‘process of appropriation of space’ and its linguistic ‘marking’.